Autocracia versus democracia en México. El rol de las Instituciones 2018-2025 - Ávila Rivera, Miriam Yolanda (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Each electoral period, new actors and/or political factors emerge that enter the political life of the country in a direct way, but what actions exercised by these factors contribute more to other forms of government? And what does it add or what does it subtract from the country's democracy? In this sense, reflection and political self-criticism among citizens is necessary to have an institutionalist approach in the executive power and not to be carried away by the oratory of political representatives, to analyze what role the media, international markets play as counterweights of power and how their influence affects or consolidates political power and its form of government. There is a triple "D" that affects democracy; misinformation, disinterest and distraction. Disinformation by fake news on social networks or on the main digital platforms. Disinterest on the part of the political parties, as they do not have a significant presence among the citizens and thus increase their disillusionment with democracy in the country. And finally, the distraction on the part of citizens by not getting involved in the country's politics and using social networks not for information, but for leisure; leaving the responsibility of electing representatives to a minimum percentage of the population. In recent years, the vision of democracy as a form of government has been reformed, in the face of a resurgence of autocratic regimes that call themselves democratic. This political-social phenomenon raises questions about the viability of both forms of government and the future of democracy in Mexico, in the context of safeguarding the most fundamental rights, it is necessary to analyze the role of institutions and their responsibility to strengthen democracy, which is the form of government constitutionally established in Mexico.

Cada periodo electoral, surgen nuevos actores y/o factores políticos que incursionan en la vida política del país de una manera directa, pero ¿Qué acciones ejercidas por estos factores contribuyen más a otras formas de gobierno? ¿Y qué suma o qué resta a la democracia del país? En este sentido, es necesaria la reflexión y la autocrítica política entre los ciudadanos para tener un enfoque institucionalista en el poder ejecutivo y no dejarnos llevar por la oratoria de los representantes políticos, analizar qué papel juegan los medios de comunicación, los mercados internacionales cómo contrapesos de poder y cómo su influencia afecta o consolida el poder político y su forma de gobierno. Existe una triple “D” qué afecta la democracia; desinformación, desinterés y distracción. La desinformación por parte de las noticias falsas en redes sociales o en las principales plataformas digitales. Desinterés por parte de los partidos políticos, al no tener una presencia significativa en los ciudadanos y así acrecentar una desilusión por parte de estos hacía la democracia en el país. Y finalmente la distracción por parte de los ciudadanos al no involucrarse en la política del país y utilizar las redes sociales no de manera informativa, sino de ocio; dejando la responsabilidad de elegir a los representantes a un mínimo de porcentaje poblacional. En los últimos años, se ha reformado la visión sobre la democracia cómo forma de gobierno, ante un resurgimiento de regímenes autocráticos que se autodenominan democráticos. Este fenómeno político- social plantea interrogantes sobre la viabilidad de ambas formas de gobierno y el futuro de la democracia en México, en el contexto de salvaguardar los derechos más fundamentales, es necesario analizar el papel de las instituciones y su responsabilidad para fortalecer la democracia qué es la forma de gobierno establecida constitucionalmente en México.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2025-1696; Ciencias políticas; Democracia; Autocracia; Instituciones; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19506